The Protein Arginine Methylase 5 (PRMT5/SKB1) Gene Is Required for the Maintenance of Root Stem Cells in Response to DNA Damage. (20th April 2016) - Li, Qiuling; Zhao, Yan; Yue, Minghui; Xue, Yongbiao; Bao, Shilai
Abstract: Plant root stem cells and their surrounding microenvironment, namely the stem cell niche, are hypersensitive to DNA damage. However, the molecular mechanisms that help maintain the genome stability of root stem cells remain elusive. Here we show that the root stem cells in the skb1 ( Shk1 kinase binding protein 1 ) mutant undergoes DNA damage-induced cell death, which is enhanced when combined with a lesion of the Ataxia-telangiectasia mutated (ATM) or the ATM/RAD3-related (ATR) genes, suggesting that the SKB1 plays a synergistically effect with ATM and ATR in DNA damage pathway. We also provide evidence that SKB1 is required for the maintenance of quiescent center (QC), a root stem cell niche, under DNA damage treatments. Furthermore, we report decreased and ectopic expression of SHORTROOT ( SHR ) in response to DNA damage in the skb1 root tips, while the expression of SCARECROW ( SCR ) remains unaffected. Our results uncover a new mechanism of plant root stem cell maintenance under DNA damage conditions that requires SKB1.